2013
DOI: 10.1590/s1984-82502013000400008
|View full text |Cite
|
Sign up to set email alerts
|

Punica granatum L. protects mice against hexavalent chromium-induced genotoxicity

Abstract: This study investigated the chemoprotective effects of Punica granatum L. (Punicaceae) fruits alcoholic extract (PGE) on mice exposed to hexavalent chromium [Cr(VI)]. Animals were pretreated with PGE (25, 50 or 75 mg/kg/day) for 10 days and subsequently exposed to a sub-lethal dose of Cr(VI) (30 mg/kg). The frequency of micronucleated polychromatic erythrocytes in the bone marrow was investigated and the Cr(VI) levels were measured in the kidneys, liver and plasm. For the survival analysis, mice were previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…In this regard, we demonstrated that the Punica granatum L. (Punicaceae) fruits reduce biological levels of Cr, increases the survival of exposed mice and protects them from Cr(VI)-induced genotoxicity ( Avila et al 2013). We also showed that Campomanesia adamantium (Cambess.)…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In this regard, we demonstrated that the Punica granatum L. (Punicaceae) fruits reduce biological levels of Cr, increases the survival of exposed mice and protects them from Cr(VI)-induced genotoxicity ( Avila et al 2013). We also showed that Campomanesia adamantium (Cambess.)…”
Section: Discussionmentioning
confidence: 84%
“…For other assays, the doses chosen were 50, 100 and 200 mg/kg/d EDE and 30 mg/kg Cr(VI) (single sublethal dose). The Cr(VI) doses were chosen according to previous studies realized by our group ( Avila et al 2013). …”
Section: Treatment/exposurementioning
confidence: 99%
See 1 more Smart Citation
“…The pomegranate is an infructescence of the pomegranate (Punica granatum), this species is capable of promoting post-implantation abortion (PROMPROM, et al, 2010;MEMARZADEH, et al, 2015). However, it does not have mutagenic potential (VALADARES et al, 2010;ÁVILA et al, 2013). It is suggested the prenatal intake of pomegranate juice due to its fetoprotective action (CHEN, et al, 2012; CHEN, LONGTINE and NELSON, 2013).…”
Section: Pomegranatementioning
confidence: 99%
“…The variation in biological monitoring techniques is sufficient to encompass the use of various species, believed to be active biological monitors (Güez et al, 2012;Ávila et al, 2013). The use of superior plants such as angiosperms, in biomonitoring studies has grown sharply (Santos, 2015).…”
Section: Introductionmentioning
confidence: 99%